Granulomatosis with polyangiitis can cause periaortitis and pericarditis. Issue 10 (11th September 2017) - Miyawaki, Mari; Oda, Seitaro; Hirata, Kenichiro; Yuki, Hideaki; Utsunomiya, Daisuke; Hayashi, Hidetaka; Sakamoto, Yasumiko; Okamoto, Shinichiro; Fujii, Kazuhiko; Yamashita, Yasuyuki
Key Clinical Message: Granulomatosis with polyangiitis (GPA) is characterized by necrotizing granulomatous inflammation usually involving the upper and lower respiratory tracts and necrotizing vasculitis predominantly affecting small‐sized vessels. Although categorized as a small vessel vasculitis, GPA can cause periaortitis and pericarditis. Physicians should recognize all categories of vasculitis can affect any size arteries. Abstract : Granulomatosis with polyangiitis (GPA) is characterized by necrotizing granulomatous inflammation usually involving the upper and lower respiratory tracts and necrotizing vasculitis predominantly affecting small‐sized vessels. Although categorized as a small vessel vasculitis, GPA can cause periaortitis and pericarditis. Physicians should recognize all categories of vasculitis can affect any size arteries.